Intrapulmonary Percussive Ventilation as an Airway Clearance Technique during Venoarterial Extracorporeal Life Support in an Infant with Pertussis - Krawiec, Conrad; Ballinger, Ken; Halstead, E. Scott (Frontiers in Pediatrics, 2017)
Initiation of extracorporeal life support is often followed by complete opacification of pulmonary parenchyma and volume loss. The optimal mechanical ventilator management and lung recruitment strategy of a pediatric patient requiring extracorporeal membrane oxygenation is not known. We present a case of a 4 week old infant who developed a severe pertussis infection requiring extracorporeal life support. The severity of his illness and pertussis infection associated intraluminal bronchiole obstruction made medical management challenging. In addition to lung protection ventilator strategies and bronchoscopy, intrapulmonary percussive ventilation was initiated to facilitate lung recruitment. This was associated with precipitous incremental improvement in lung compliance and eventual liberation from venoarterial extracorporeal life support.